ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA CV. KURNIA ADI PERKASA SURABAYA - Efianti Wibowo, Sarah; Rusmawati, Zeni; Surahman, Dedy (SUSTAINABLE, 2024)
This paper examines the implementation of the internal control system for merchandise inventory at CV. Kurnia Adi Perkasa Surabaya. The type of research used in this research is a type of qualitative research with descriptive research methods. Data collection techniques in this study were in the form of observation, interviews, and documentation using analytical tools for internal control elements consisting of: 1) organizational structure that clearly separates functional responsibilities, 2) authorization systems and recording procedures, 3) practice healthy, and 4) employees whose quality is in accordance with their responsibilities. The results of the study of the internal control system in the procedure for managing merchandise inventory implemented by CV. Kurnia Adi Perkasa Surabaya is sufficient. However, there are still some that are not in accordance with the elements of internal control according to theory where there are multiple tasks in running the organization and some documents are not authorized by the proper party and there are stock differences due to lack of accuracy and negligence of related functions.